Analysis of protein kinase A activity in insulin-secreting cells using a cell-penetrating protein substrate and capillary electrophoresis - Rauf, Femina (2010)
A cell-penetrating, fluorescent protein substrate was developed to monitor intracellular protein kinase A (PKA) activity in cells without the need for cellular transfection. The PKA substrate (PKAS) was prepared with a 6×histidine purification tag, an enhanced green fluorescent protein (EGFP) reporter, an HIV-TAT protein transduction domain for cellular translocation and a pentaphosphorylation motif specific for PKA. PKAS was expressed in Escherichia coli and purified by metal affinity chromatography. Incubation of PKAS in the extracellular media facilitated translocation into the intracellular milieu in HeLa cells, βTC-3 cells and pancreatic islets with minimal toxicity in a time and concentration dependent manner. Upon cellular loading, glucose-dependent phosphorylation of PKAS was observed in both βTC-3 cells and pancreatic islets via capillary zone electrophoresis. In pancreatic islets, maximal PKAS phosphorylation (83± 6%) was observed at 12 mM glucose, whereas maximal PKAS phosphorylation (86±4%) in βTC-3 cells was observed at 3 mM glucose indicating a left-shifted glucose sensitivity. Increased PKAS phosphorylation was observed in the presence of PKA stimulators forskolin and 8-Br-cAMP (33% and 16%, respectively), with corresponding decreases in PKAS phosphorylation observed in the presence of PKA inhibitors staurosporine and H-89 (40% and 54%, respectively).